Avaliação das variações da temperatura na produção de biogás em biodigestores Bioköhler durante inverno e primavera - Tavares, Sidnei Gregório (2015)
The experiment was conducted at the Experimental Station Antonio Carlos dos Santos Pessoa, which belongs to UNIOESTE - Campus Marechal Cândido Rondon, from July 29 to December 1, 2013. The experiment aimed to verify the influence of climate variations in the production of biogas. The continuous flow biodigester BioKöhler model, with useful capacity of 19.56 m³, was daily fed with cattle manure and 30 kg of poultry litter. There were daily measured the volume and density of the manure of cattle and the volume of biogas. Internal temperatures were recorded every 15 minutes and the rest of the information was acquired from weather station which is next to the digester. Evaluating the results it was observed that there is a positive correlation in all the evaluated factors. External and internal temperature, rainfall and solar radiation interfere in the production of biogas, but the interference of rain was determined to be negligible and the temperature inside the biodigester is the factor with the greatest influence in the production of biogas. It was possible to produce daily average of 10 m³ of biogas with the daily addition of 36 kg of volatile solids in a hydraulic retention time of 37 days.